Post-zygotic ACTB mutations underlie congenital smooth muscle hamartomas. - Atzmony, Lihi; Ugwu, Nelson; Zaki, Theodore D; Antaya, Richard J; Choate, Keith A (J Cutan Pathol, 2020)
BACKGROUND: Congenital smooth muscle hamartomas (CSMHs) are benign lesions that share clinical and histopathological features with Becker nevus, a mosaic disorder associated with post-zygotic ACTB mutations. Given the clinical and histopathological overlap between CSMH and Becker nevus, we hypothesized that post-zygotic mutations in ACTB may underlie CSMH. METHODS: Direct sequencing of ACTB gene in affected and unaffected tissue isolated from one case of hemihypertrichosis and hemihypertrophy corresponding to giant segmental CSMH and hemihypertrophy. This was followed by direct sequencing with and without enrichment assay for hotspot ACTB mutations in affected tissue from 12 samples of isolated CSMH from unrelated individuals. RESULTS: In total we identified somatic missense ACTB mutations in 9 out of 13 CSMHs (69%). Mutations were either novel or previously reported in Becker nevi and Becker nevus syndrome. CONCLUSIONS: CSMHs result from post-zygotic ACTB mutations. This study proves that CSMHs and Becker nevi are nosologically related, and expand the phenotypic spectrum of ACTB mutations.

Two percent lovastatin ointment as a pathogenesis-directed monotherapy for porokeratosis. - Ugwu, Nelson; Choate, Keith A; Atzmony, Lihi (JAAD Case Rep, 2020)